Clostridium septicum infection complicating Hemolytic-Uremic Syndrome: a case report and review of the literature - Cirillo, Luigi; Noris, Alice; Odone, Ludovica; Giordano, Flavio; Becherucci, Francesca (Journal of nephrology, 2024)
Clostridium septicum ( C. septicum ) is a zoonotic bacillus found in 2.8% of healthy human stools. In humans, it can cause serious infections such as bacteremia, myonecrosis, and encephalitis by spreading through the bloodstream. Reports of Shiga toxin-producing Escherichia Coli-related hemolytic-uremic syndrome complicated by C. septicum superinfection are rare, likely because colonic microangiopathic lesions by Shiga toxin-producing Escherichia Coli facilitate bacterial dissemination. Only 13 cases of Shiga toxin-producing Escherichia Coli-related hemolytic-uremic syndrome with C. septicum superinfection have been reported to date, according to our litterature review, with a 50% mortality rate. The lack of clinico-laboratory clues suggesting this condition makes the diagnosis challenging. For these reasons C. septicum superinfection usually goes undiagnosed in patients with Shiga toxin-producing Escherichia Coli-related hemolytic-uremic syndrome, and results in unfavorable outcomes. In this paper, we describe the case of a 5-year-old girl admitted for Shiga toxin-producing Escherichia Coli-related hemolytic-uremic syndrome who developed C. septicum coinfection leading to a fatal outcome. We carried out a review of the available literature on C. septicum infection complicating Shiga toxin-producing Escherichia Coli-related hemolytic-uremic syndrome and we compared the clinical features of the observed cases with those of an historical cohort of uncomplicated Shiga toxin-producing Escherichia Coli-related hemolytic-uremic syndrome. The mechanisms of superinfection are still unclear and clinical features are indistinguishable from those of uncomplicated Shiga toxin-producing Escherichia Coli-related hemolytic-uremic syndrome. However, rapid deterioration of clinical conditions and evidence of neurological involvement, associated with abnormal radiological findings, require immediate management. Although therapeutic approaches have not been directly compared, neurosurgical treatment of amenable lesions may improve the clinical outcome of patients with C. septicum -hemolytic-uremic syndrome.